Inhibition of organic cation transporter (OCT) activities by carcinogenic heterocyclic aromatic amines. (February 2019) - Sayyed, Katia; Camillerapp, Christophe; Le Vée, Marc; Bruyère, Arnaud; Nies, Anne T.; Abdel-Razzak, Ziad; Fardel, Olivier
Abstract: Carcinogenic heterocyclic aromatic amines (HAAs) interact with some drug transporters, like the efflux pump BCRP and the organic anion transporters OAT1 and OAT3. The present study was designed to determine whether they can also target activities of the organic cation transporters (OCTs), using mainly OCT1-, OCT2- and OCT3-overexpressing HEK293 cells. Fifteen HAAs were demonstrated to differently alter OCT activities; with a cut-off of at least 50% reduction of transporter activity by 100 μM HAAs, 5/15 HAAs, including Trp-P-1 and Trp-P-2, inhibited activities of OCT1, OCT2 and OCT3, whereas 7/15 HAAs, including PhIP and MeIQx, blocked those of OCT2 and OCT3, 1/15 HAAs reduced those of OCT1 and OCT2 and 2/15 HAAs, including AαC, only that of OCT2. IC50 values of Trp-P-1 and Trp-P-2 towards OCT activities were found to be in the 2–6 μM range, likely not relevant for human exposure to HAAs through smoking or the diet. Trp-P-1 and Trp-P-2 additionally failed to trans -stimulate OCT1 and OCT2 activities and exhibited similar accumulation in OCT1/2-transduced HEK293 cells and control HEK293-MOCK cells. These data demonstrate that HAAs, notably Trp-P-1 and Trp-P-2, interact with OCT1/2, without however being transported, thus likely discarding a major role for OCT1/2 in HAA systemic toxicokinetics. Highlights: Various HAAs inhibit activity of the organic cation transporters OCT1, OCT2 and OCT3. Trp-P-1 and Trp-P-2 are ones of the most active HAAs against OCT activities. HAA IC50 towards OCTs are higher than expected HAA concentrations in humans. Trp-P-1 and Trp-P-2 are not substrates for OCT1 and OCT2.